Bimetallic Gold-Palladium Nanoparticles: Applications in Methanol and Ethanol Oxidation Reactions. (1st October 2022) - Parkash, Anand; Islam, Mazharul; Pirzada, Abdul Majeed; Qureshi, Khan Muhammad
Abstract : Methanol oxidation reaction (MOR) generates renewable energy. This method of generating energy makes use of small Pt-Ru catalysts. The cost of fuel cell technology makes it unsuitable for widespread use. Like platinum, palladium has electrocatalytic properties. In-situ CO poisons its monometallic form, which possesses significant overpotentials. Alkaline electrolytes, unfavorable for platinum but speed up the kinetics of alcohol oxidation by preferentially oxidizing methanol to formaldehyde, are where palladium is most active. Secondary metals collaborate in the co-catalysis of CO surface oxidation and assist in controlling palladium-reactant binding strengths. An article discusses anode electrocatalysts. The mechanics of current platinum catalysts are compared to those of palladium catalysts. Palladium catalyst requirements and synthesis are discussed.